Acute Generalized Exanthematous Pustulosis (AGEP) in 12 Patients Treated for SARS-CoV-2 Positive Pneumonia. (May 2021) - Pezzarossa, Enrico; Ungari, Marco; Caresana, Gioachino; Sagradi, Fabio; Cimardi, Leonardo; Pan, Angelo; Testa, Sophie; Aguggini, Sergio; Varotti, Elena; Tanzi, Giulia; Manotti, Laura; Ferrero, Giuseppina; et al.
Abstract : Abstract: The novel coronavirus disease 2019 (COVID-19) caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is rapidly spreading throughout the world. The study describes 12 patients with SARS-CoV-2 pneumonia, who developed an acute erythematous rash with nonfollicular pinhead-sized pustules, without mucosal involvement. The clinical differential diagnosis was viral rash, acute generalized exanthematous pustulosis (AGEP), or multiform erythema. computed tomography with a diagnosis of interstitial pneumonia and a respiratory tract sample positive for SARS-CoV-2 in a reverse transcriptase polymerase chain reaction assay. Patients had signs of respiratory distress and were treated with hydroxychloroquine, darunavir, ritonavir, heparin, ceftriaxone, and azithromycin. Punch biopsies showed subcorneal pustules typical of AGEP. Dermal microvascular injury and thrombosis as described in skin damage by SARS-CoV-2 infection was not observed. The direct immunofluorescence for IgG, IgA, IgM, and C3 was negative in 8 patients investigated. A polymerase chain reaction for RNA SARS-CoV-2 performed on frozen skin was negative in 5 of 6 patients. Most of our patients were treated with systemic corticosteroids. After some days (4–10), the diffuse erythema and pustules had improved. AGEP is classified as a severe cutaneous adverse reaction, provoked by drugs and acute infections. Characteristically, removal of the offending agent leads to spontaneous resolution typically in less than 15 days. The recognition of AGEP is important, in order to avoid confusion with a systemic infection and consequently to avoid incorrect treatment. Cutaneous adverse reactions to drugs are common and are major health problems worldwide causing considerable costs for health care systems. We suggest that in the patients with AGEP during SARS-CoV-2 pneumonia, viral infection is a risk factor for developing drug reaction.